2015
DOI: 10.1103/physrevlett.114.060603
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Fluctuations for a Single-Particle Analog of Gas in a Soft Wall

Abstract: We investigate the motion of a colloidal particle driven out of equilibrium by a time-varying stiffness of the optical trap that produces persistent nonequilibrium work. Measurements of work production for repeated cycles composed of the compression and expansion processes for the optical potential show huge fluctuations due to thermal motion. Using a precise technique to modulate the stiffness in time, we accurately estimate the probability distributions of work produced for the compression and expansion proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
2
22
1
Order By: Relevance
“…5(b). The shortest updating time in previous study [28] was 1 ms (~1/10 of their quasistatic limit), which is 100 times larger than =10 s (1/1000 of quasistatic limit) in this study. Therefore, in comparison to the previous study which could test the validity of the Crooks fluctuation theorem only a little off the equilibrium state, current study demonstrated its validity in highly nonequilibrium regimes as well.…”
Section: Nonequilibrium Fluctuations In Time-varying Harmonic Potentialcontrasting
confidence: 58%
“…5(b). The shortest updating time in previous study [28] was 1 ms (~1/10 of their quasistatic limit), which is 100 times larger than =10 s (1/1000 of quasistatic limit) in this study. Therefore, in comparison to the previous study which could test the validity of the Crooks fluctuation theorem only a little off the equilibrium state, current study demonstrated its validity in highly nonequilibrium regimes as well.…”
Section: Nonequilibrium Fluctuations In Time-varying Harmonic Potentialcontrasting
confidence: 58%
“…First, we clearly see ρ ss ( r, v) = ρ ss ( r, − v) from position-velocity coupling in Eq. (23). Second, we find a nonzero irreversible current in Eq.…”
Section: Non-equilibrium Probability Currentsmentioning
confidence: 62%
“…There have been many studies on non-equilibrium fluctuation driven by external non-equilibrium sources such as non-conservative forces and time-dependent protocols which produce work and heat persistently [1][2][3][4][5][6][7][8][9][10][11][12][13]. There have been extensive experimental studies, measuring work and confirming the FT [14][15][16][17][18][19][20][21][22][23]. Under a particular circumstance, there exists a non-equilibrium steady state (NESS) characterized by non-Boltzmann distribution, non-zero current, non-zero rate of perpetual heat or work production, etc.…”
Section: Introductionmentioning
confidence: 99%
“…101 Dynamical optical traps have also been used to test fundamental issues of nonequilibrium thermodynamics. 102 The practical ease of this technology, and the multiple uses to which it can be put, make it likely that research exploiting optical control of colloid-colloid interactions will advance in prominence.…”
Section: Future Prospectsmentioning
confidence: 99%